Comparison between Hemiarthroplasty in the First Proximal Phalanx and Keller's Arthroplasty. A Finite Element Study - Madrid Pérez, Mario Alberto; Bayod López, Javier (Jornada de Jóvenes Investigadores del I3A, 2018)
Hallux valgus and hallux rigidus are the most common pathologies in the first ray of the foot. Arthroplasty can restore the mobility of the joint but is a destructive procedure. This paper presents three finite element analysis of the foot studying two different kinds of arthroplasty.